DEVELOPMENT OF TEACHING MATERIALS FOR STAD-TYPE COOPERATIVE MODELS WITH BLENDED LEARNING METHOD ON MATERIAL SYSTEMS OF LINEAR EQUATIONS - Ahmad Talib; Yulianti Para'pak (Universitas Negeri Makassar, 2022)
Learning and teaching materials are two things that complement each other. Learning will work if equipped with teaching materials such as textbooks and LKM. The learning process must be able to increase the independence and creativity of students so that their skills are more focused and produce output that is ready to face challenges in the 21st century. One of the alternative 21st-century learning methods that is appropriate to use is the blended learning method . The implementation of the blended learning method will work effectively if it is equipped with teaching materials such as textbooks and LKM as reference materials for students in learning. Therefore, in this study developed STAD type cooperative teaching materials with the blended learning method . The method used in this research is Nieveen's (1999) development method which includes the initial investigation stage, the prototype stage, and the assessment stage. The results of the development showed that: (1) the expert's assessment of the STAD cooperative model teaching materials (textbooks and LKM) with the blended learning method was feasible to use, (2) the trial results of the STAD cooperative model teaching materials with the blended learning method were practically used by lecturers and students in learning and effective for students mastering the material system of linear equations.